DEVELOPMENT OF LMS PHYTAGORAS BASED TERPADU AS CAPABILITY BOOSTER MATHEMATIC NUMERACY - Wiwit Damayanti Lestari; Diki Mulyana; Nandang Nandang (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Integrated Hybrid Learning Development Research aims to develop Integrated Hybrid Learning, Active, Simple, and Collaborative, abbreviated as LMS Phytagoras, based on TERPADU (Telaah, Eksplorasi, Rumuskan, Presentasikan, Aplikasikan, Duniawi, dan Ukhrowi) as a means to strengthen numeracy skills with valid and effective criteria. The subjects of this study were third-semester students of Mathematics Education at Wiralodra University, specifically in the selected topics course of secondary mathematics education. The type of research utilized in this study is Research and Development (R&D). The design model used is the ADDIE type. The data collection instruments include validation sheets, tests, and questionnaires. During the validation process, LMS Phytagoras was validated by three expert validators with medium validity criteria. LMS Phytagoras was implemented by 7 students, resulting in medium effectiveness of learning as determined by pretest and posttest results using the n-gain test. LMS Phytagoras received positive responses from students in TERPADU-based learning.